JNK signaling and integrins cooperate to maintain cell adhesion during epithelial fusion in Drosophila - Karkali, Katerina; Pastor-Pareja, Jose Carlos; Martin-Blanco, Enrique (Frontiers in Cell and Developmental Biology, 2024)
The fusion of epithelial sheets is an essential and conserved morphogenetic event that requires the maintenance of tissue continuity. This is secured by membrane-bound or diffusible signals that instruct the epithelial cells, in a coordinated fashion, to change shapes and adhesive properties and when, how and where to move. Here we show that during Dorsal Closure (DC) in Drosophila, the Jun kinase (JNK) signaling pathway modulates integrins expression and ensures tissue endurance. An excess of JNK activity, as an outcome of a failure in the negative feedback implemented by the dual-specificity phosphatase Puckered (Puc), promotes the loss of integrins [the ß-subunit Myospheroid (Mys)] and AS detachment. Likewise, integrins signal back to the pathway to regulate the duration and strength of JNK activity. Mys is necessary for the regulation of JNK activity levels and in its absence, puc expression is downregulated and JNK activity increases.